Social political changes in 70’s Turkey and its reflections on turkish foreign policy - Bilgin, Gizem (My University, 2007)
1970-80 yılları Türk siyasal yaşamı için önemli bir dönemi oluşturmaktadır. Bu dönemin farklılığı dünya politikasını etkileyen Soğuk Savaş dinamiklerinin ötesinde ideolojik uyanışlara bağlı olarak yaşanan sosyal dönüşüm ve politik kültürdeki değişimdir. Bu süreçte, 1961 Anayasasının kamusal alanda göreceli olarak yarattığı özgürlük ortamı, sosyal yaşama güçlü şekilde nasıl yansıdığını, iktidar ve muhalefet tarafından nasıl algılanıp politika oluşum sürecine nasıl aktarıldığı görülebilmektedir. Anarşinin varolduğu ve devletlerin güç dengesiyle biçimlediği uluslalararası sistem anlayışının aksine, sosyal politik ve ekonomik değişimleri kapsayan iç siyasal gelişmeler ve kamuoyunun devlet dışı yapılarlara politika oluşum sürecine katılımı uluslararası ilişkiler literatürünün yeni yaklaşımı olmuştur. Bu bağlamda liberal düşüncenin inceleme alanı olarak gördüğü kalkınmış liberal demokratik yapılarında ötesinde bu çalışma iç siyasal dinamiklerin Türk dış politikasının oluşum sürecinde belirleyici olduğu araştırmanın temel sorusudur. Bu süreç Türkiye Büyük Millet Meclisinde 1971 -1980 arası yapılan Dışişleri bakanlığı Bütçe görüşmeleri tutanakları incelenerek değerlendirilecektir.

The importance of the period 1970-80 in Turkish political history not only comes from the reflections of the Cold War period in World Politics but also from the new ideological awakenings and social transformation of the society and Turkish political culture. Most dominant force for these changes is the relative political freedom which 1961 Constitution had built in public life and how it’s perceived by the political elite in the power and in the opposition. According to new international approaches adversely to system based idea of an anarchic structure controlled by state power equilibrium (realist and neo-realist theories), domestic structures enclosing social, political and economical changes and public opinion involvement by non-state structures to policy making procedures had evaluated international environment. In case of the narrow understanding of the liberal approach just looking from state centric view from liberal developed countries this research want to analyze an important decade for Turkish foreign policy building that had highly affected by domestic structures and public opinion. Due to that, this research will answer the question of how these changes affect the decision making mechanisms in domestic political events and how these effects shaped the Turkish foreign policy in 1970’s world by analysing Turkish Foreign Ministry Budget discussions in General Assembly between 1971-1980.
Keywords: Siyaset ve Yönetim; Türkiye_ Dış Politika